Nationwide surveillance of bacterial respiratory pathogens conducted by the surveillance committee of Japanese Society of Chemotherapy, the Japanese Association for Infectious Diseases, and the Japanese Society for Clinical Microbiology in 2010: General view of the pathogens' antibacterial susceptibility. Issue 6 (June 2015) - Yanagihara, Katsunori; Kadota, Junichi; Aoki, Nobuki; Matsumoto, Tetsuya; Yoshida, Masaki; Yagisawa, Morimasa; Oguri, Toyoko; Sato, Junko; Ogasawara, Kazuhiko; Wakamura, Tomotaro; Sunakawa, Keisuke; Watanabe, Akira; et al.
Abstract: The nationwide surveillance on antimicrobial susceptibility of bacterial respiratory pathogens from patients in Japan, was conducted by Japanese Society of Chemotherapy, Japanese Association for Infectious Diseases and Japanese Society for Clinical Microbiology in 2010. The isolates were collected from clinical specimens obtained from well-diagnosed adult patients with respiratory tract infections during the period from January and April 2010 by three societies. Antimicrobial susceptibility testing was conducted at the central reference laboratory according to the method recommended by Clinical and Laboratory Standard Institutes using maximum 45 antibacterial agents. Susceptibility testing was evaluable with 954 strains (206 Staphylococcus aureus, 189 Streptococcus pneumoniae, 4 Streptococcus pyogenes, 182 Haemophilus influenzae, 74 Moraxella catarrhalis, 139 Klebsiella pneumoniae and 160 Pseudomonas aeruginosa ). Ratio of methicillin-resistant S. aureus was as high as 50.5%, and those of penicillin-intermediate and -resistant S. pneumoniae were 1.1% and 0.0%, respectively. Among H. influenzae, 17.6% of them were found to be β-lactamase-non-producing ampicillin (ABPC)-intermediately resistant, 33.5% to be β-lactamase-non-producing ABPC-resistant and 11.0% to be β-lactamase-producing ABPC-resistant strains. Extended spectrum β-lactamase-producing K. pneumoniae and multi-drug resistant P. aeruginosa with metallo β-lactamase were 2.9% and 0.6%, respectively. Continuous national surveillance of antimicrobial susceptibility of respiratory pathogens is crucial in order to monitor changing patterns of susceptibility and to be able to update treatment recommendations on a regular basis.